Corporate leverage preferences: some evidence from Greek firms - Βασιλείου Δημήτριος; Κοντολαίμος Γρηγόριος (SPOUDAI Journal of Economics and Business, 2005)
The paper presents empirical evidence on the determinants of capital structure of listed Greek firms from 1997 to 2001. We use panel data for a sample of 138 firms listed in Athens Stock Exchange. The hypothesis that is tested in this paper is that the leverage ratio depends upon eight explanatory variables: liquidity, asset structure, interest coverage ratio, profitability, firm size, effective tax rate, risk and Tobin's q. We apply the three following models in order to estimate the effevt of each independent variable in leverage: the total model, the fixed effects model and the random effects model. The main conclusion from this study is that firms prefer internal from external financing. This is a hint that peching order may exist. However, when it comes to external financing there is no evidence that firms prefer dept to equity. Modt of the results are consistent with the theoretical background, which is presented in the secod section of the paper. JEL Classifications: G3, G32